Property in Social Continuity. - Benda-Beckmann F. von (Brill, 1979)
This book deals with the property and inheritance system of the matrilineal Minangkabau of West Sumatra in the context of legal pluralism.
Keywords: Minangkabau (Indonesian people); Inheritance and succession (Islamic law) -- Indonesia -- Sumatera Barat.; Inheritance and succession (Adat law); Minangkabau (Peuple d'Indonésie); Successions et héritages (Droit islamique) -- Indonésie -- Sumatera Barat.; Successions et héritages (Droit adat); Asian history.; History.; Humanities.; Regional and national history.; Inheritance and succession (Islamic law); Indonesia -- Sumatera Barat; indonesia.